2018
DOI: 10.1155/2018/5120974
|View full text |Cite
|
Sign up to set email alerts
|

Image Quality and Patient-Specific Organ Doses in Stone Protocol CT: A Comparison of Traditional CT to Low Dose CT with Iterative Reconstruction

Abstract: Objective To compare organ specific radiation dose and image quality in kidney stone patients scanned with standard CT reconstructed with filtered back projection (FBP-CT) to those scanned with low dose CT reconstructed with iterative techniques (IR-CT). Materials and Methods Over a one-year study period, adult kidney stone patients were retrospectively netted to capture the use of noncontrasted, stone protocol CT in one of six institutional scanners (four FBP and two IR). To limit potential CT-unit use bias, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…8,9 Low-dose scans have been shown to have 59% lower organ-specific radiation compared with standard CT with no loss of image quality. 5,10 More recently, ultra-low-dose CT (ULD CT) protocols, which use even less ionizing radiation than lowdose CT, have been developed. A systematic review demonstrated that ULD CT (<1.9 mSv) and low-dose CT (<3.5 mSv) have comparable sensitivity (90%-96%) and specificity (97%-99%) for ureteral stones.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Low-dose scans have been shown to have 59% lower organ-specific radiation compared with standard CT with no loss of image quality. 5,10 More recently, ultra-low-dose CT (ULD CT) protocols, which use even less ionizing radiation than lowdose CT, have been developed. A systematic review demonstrated that ULD CT (<1.9 mSv) and low-dose CT (<3.5 mSv) have comparable sensitivity (90%-96%) and specificity (97%-99%) for ureteral stones.…”
Section: Introductionmentioning
confidence: 99%
“…12,22 The long-term risks of high radiation exposure become a concern in those patients undergoing repeated CTs for recurrent urolithiasis, particularly with regard to the development of secondary malignancy. 8,23 Furthermore, CT examinations are being performed more frequently as imaging services become increasingly accessible. 24 LD-CTKUB protocols for urolithiasis have been investigated in several studies, with several having an effective dose of <2.0 mSv.…”
Section: Discussionmentioning
confidence: 99%
“…Ongoing follow up forms an important component of its management with CT imaging being the established, gold‐standard approach 12,22 . The long‐term risks of high radiation exposure become a concern in those patients undergoing repeated CTs for recurrent urolithiasis, particularly with regard to the development of secondary malignancy 8,23 . Furthermore, CT examinations are being performed more frequently as imaging services become increasingly accessible 24 …”
Section: Discussionmentioning
confidence: 99%
“…Time has witnessed the development of the reconstruction algorithms during these years. Conventional ltered back projection (FBP) reconstruction technique has been well received due to its quick imaging technology for decades [36]. Iterative reconstruction (IR) algorithms have been introduced to improve image quality with less image noise [37][38].…”
Section: Discussionmentioning
confidence: 99%